Emergence of rifampin-resistant Rhodococcus equi in an infected foal. - Takai, S (1997)
To investigate the emergence of rifampin resistance in Rhodococcus equi strains isolated from foals and their environment in Japan, we compared the in vitro antimicrobial susceptibilities to rifampin of 640 isolates from 64 infected foals and 98 soil isolates from their horse-breeding farms. As a control, 39 human isolates from patients with and without AIDS were also tested for susceptibility to rifampin. All of the isolates showed rifampin sensitivity, except isolates from one infected foal and two patients with AIDS that showed rifampin resistance. To investigate the emergence of rifampin-resistant R. equi in the infected foal, which had received rifampin monotherapy for a month before euthanasia, 99 isolates of R. equi from the lesions and 20 isolates from the intestinal contents of the one foal with rifampin-resistant organisms were analyzed for rifampin susceptibilities, pathogenicities, and ribotypes. Of the 99 isolates from the lesions, all of which were virulent R. equi strains containing a virulence plasmid with a size of 85 or 90 kb, 90 (91%) isolates were rifampin resistant (MIC, > or = 12.5 microg/ml). On the other hand, of the 20 isolates from the intestinal contents, 11 (55%) isolates showed rifampin resistance (MIC, > or = 25 microg/ml), and 5 of them were avirulent R. equi strains. Among these 101 rifampin-resistant R. equi isolates with and without virulence plasmids characterized by ribotyping, 58 were type I, 20 were type II, 11 were type III, and 12 were type IV. These results demonstrated that at least eight different rifampin-resistant R. equi strains emerged concurrently and respectively from the different lesions and intestinal contents of the infected foal.